2013
DOI: 10.3892/mmr.2013.1742
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin reverses multidrug resistance of HepG2/ADR human hepatoma cells via downregulation of MDR1 and P-glycoprotein expression

Abstract: Multidrug resistance (MDR) of tumor cells is a serious obstacle encountered in cancer treatment. In the current study a multiple drug‑resistant HepG2/adriamycin (HepG2/ADR) cell line was established and its MDR was characterized. Icaritin, an active ingredient isolated from the medical plant Herba Epimedium, was observed to reverse MDR in the present model. Icaritin significantly increased the intracellular accumulation of ADR and decreased the expression of the MDR1 gene in HepG2/ADR cells compared with drug‑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Icaritin, an active ingredient isolated from the medical plant Herba Epimedium, reverses MDR of HepG2/ADR human hepatoma cells via downregulation of MDR1 and Pgp expression (103). Pien Tze Huang, a well-known traditional Chinese medical formula, has been used in China and Southeast Asia for centuries as a folk remedy for various types of cancer.…”
Section: Kim Et Al Reported That Resveratrol Enhanced Doxorubicinindmentioning
confidence: 99%
“…Icaritin, an active ingredient isolated from the medical plant Herba Epimedium, reverses MDR of HepG2/ADR human hepatoma cells via downregulation of MDR1 and Pgp expression (103). Pien Tze Huang, a well-known traditional Chinese medical formula, has been used in China and Southeast Asia for centuries as a folk remedy for various types of cancer.…”
Section: Kim Et Al Reported That Resveratrol Enhanced Doxorubicinindmentioning
confidence: 99%
“…In various present studies, icaritin induces cell apoptosis in many solid tumors [27, 10, 11] and myeloid original malignancies [8, 9]. To determine whether icaritin induces apoptosis in lymphoid malignant cells, Raji cells were treated with different concentrations of icaritin for 48 h and Annexin V-FITC and PI fluorescence assays were performed to evaluate necrotic cells as well as early stage and late stage apoptotic cells.…”
Section: Resultsmentioning
confidence: 98%
“…Icaritin is a hydrolytic product of icariin that is extracted from Epimedium brevicornum, which is a traditional Chinese medicine (TCM). Icaritin has showed significant antitumor activities with minor side effects in various neoplasms, such as inducing apoptosis in human endometrial cancer Hec1A cells [2], leading to cell growth inhibition, G1 arrest, and apoptosis of prostate cancer PC-3 cells [3], resulting in cell cycle arrest at the G2/M phase, apoptotic cell death [4] and enhancing radio sensitivity [5] in breast cancer cells, inhibiting growth [6], and reversing multidrug resistance [7] of hepatoma HepG2 cells. For hematopoietic neoplasms, Li and his team demonstrated the antitumor effect of icaritin in acute myeloid leukemia cells [8], and we reported that icaritin showed potent antileukemia activity on chronic myeloid leukemia in vitro and in vivo [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growth inhibitory effects of the non-fractionated aqueous extract of EG demonstrated in the current study, the identity of the water-soluble bioactive agent(s) in this extract remain unclear. Methanolic extracts from EG containing icariin and icaritin have been demonstrated to effect multidrug resistance in HepG2/ADR cells (26). In contrast, the same methanol soluble bioactive agents induce growth promoting effects through the upregulation of epidermal growth factor receptor/mitogen-activated protein kinase signaling pathways in a model of HER-2 + breast cancer (27).…”
Section: Discussionmentioning
confidence: 99%